Attitude Towards Language in Sociolinguistics Settings: A Brief Overview - Amin, Ahmad (REiLA : Journal of Research and Innovation in Language, 2020)
The use of language is a form of social interaction that occurs in various situations. Social interaction will live from the activity of talking to members of the language users. Language is also a means to show self-identity. Through language, we can show our viewpoint, our origins and nations, our education level, even our nature. From the sociolinguistic perspective, language attitude in multilingual society is an interesting phenomenon to study. Language behaviour and attitude towards language are the two things that are closely related, which can determine the choice of languages as well as the survival of a language. The study of sociolinguistics is addressing the phenomena of language selection as a discourse in the event of communication and demonstrating the social and cultural identity of the speech participants. Community members are constantly changing variations in the use of language.